Parametric Study of Polypropylene Based Geotextile Mat for Optimum Performance in Engineered Landfill Systems - Ikpe, Aniekan Essienubong; Effiong, Ndon Akanu-ibiam; Mike, Etuk Ekom (Applications of Modelling and Simulation, 2020)
Polypropolyene (PP) is commonly used in geotextile mat reinforcements for landfill systems due to its unique properties which must be carefully selected to ensure adequate performance of the PP material. To achieve this, supplier information for the PP material which included tensile strength, mass and thickness were simulated as input variables for twelve scenarios each using SOLIDWORKS and Response Surface Methodology (RSM) software. The goal was to minimize stress, resultant displacement and equivalent strain to avoid the catastrophic effect that may occur when the goal is opposite. In comparison to other scenarios, RSM in the 4th scenario probed the input values by indicating that input values of 1.5 mm thickness, 3110.54 g of mass and tensile strength of 33 MPa produced optimum output values of 27418 N/m2 stress, 0.000102754 mm displacement and 0.000007452 strain. Similarly in the 7th scenario, SOLIDWORKS probed the input values by indicating that input values of 1.6 mm thickness, 3110.54 g of mass and tensile strength of 33 MPa produced optimum output values of 26984 N/m2 stress, 0.000102614 mm displacement and 0.000007152 strain. The proximity observed in the selected results generated by both software indicates a level of accuracy that can sustain the service life of the PP material in landfill applications if adopted by manufacturers.